Use of an Orthodontic and Otolaryngological Approach in an Infant with Holoprosencephaly - Angela Galeotti; Giovanni Carlo De Vincentiis; Emanuela Sitzia; Giuseppe Marzo; Wanda Maldonato; Gaia Bompiani; Maria Beatrice Chiarini Testa; Alessandra Putrino; Andrea Bartuli; Paola Festa (MDPI AG, 2024)
Holoprosencephaly is a complex human brain malformation resulting from incomplete cleavage of the prosencephalon into both hemispheres. Congenital nasal pyriform aperture stenosis (CNPAS) is sometimes found in patients with mild forms of holoprosencephaly. Surgical treatment is required. Low-invasive surgical approaches involve balloon dilation of the pyriform opening. We present the case of an 8-day-old girl diagnosed with holoprosencephaly, CNPAS, and the presence of a solitary median maxillary central incisor. Once examined by neonatologist, geneticist, pneumologist, otolaryngologist, and pediatric dentist, a combined otolaryngological-orthodontic approach was used. The obstruction of the right nasal cavity was treated by widening the nasal cavities and stabilizing them with a balloon dilation technique. After surgery, the respiratory space was increased by applying a neonatal palatal expander plate (NPEP) considering the palatal deformity: ogival shaped, anterior vertex growth direction, reduction of transverse diameters. The NPEP promoted distraction of the median palatine suture and assisted the nasal dilation. Therefore, after the insertion of NPEP, the physiological sucking-swallowing mechanism was activated. In infants with CNPAS, NPEP can be useful to ensure the safe stability of nasal dilation. A multidisciplinary approach is fundamental. In our experience, the close collaboration between an otolaryngologist and orthodontist is essential for the management of the patient with CNPAS.